(3QSGdI aj Yde GddZIs
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi ehdGfG jMJGL Edi eYQaI GdaQb Hjf GdETJHGg HYVgG HHYV hbd ef jMQQ ajgG GdebGd ef GdQLGd s
(3BNQgG (B:s
(3hLYdg GdScGci ef GdeYQha HcdGe GdNdjaI HERGA GdNUhUjGJ deG CTGQ Edjg GdSjQ GfJgi hHGddg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(505 (3O(B) s
Keywords: (3GdeLGejYs